Changes in Plasma γ-Glutamyl Transpeptidase Activity Associated with Alterations in Drug Metabolism in Man. Issue 5849 (10th February 1973) - Whitfield, J. B.; Moss, D. W.; Neale, G.; Orme, M.; Breckenridge, A.
Abstract : A significant rise in plasma γ-glutamyl transpeptidase activity (GGT) was observed on 13 out of 14 occasions on which patients on long-term treatment with the oral anticoagulant warfarin were given amylobarbitone, quinalbarbitone, or phenazone (antipyrine) for 30 days. In 13 of these 14 studies there was evidence that drug administration had stimulated the rate of warfarin metabolism. One patient showed no increase in plasma GGT activity, yet a significantly increased rate of warfarin metabolism, and another patient showed an increase in plasma GGT activity without a change in warfarin metabolism. When alterations in both plasma GGT activity and plasma warfarin concentration occurred together in response to drug administration the changes followed a similar time course, occurring after about one week of drug administration with maximal changes at about 10 or 15 days. Administration of chlordiazepoxide, diazepam, nitrazepam, and methaqualone did not stimulate the rate of warfarin metabolism in four patients studied, but plasma GGT activity increased significantly in two of these four instances. The implications of these observations in the interpretation of plasma GGT activities are discussed.